2002
DOI: 10.1253/circj.66.886
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival of Non-Elderly Patients With Severe Heart Failure Treated With Angiotensin-Converting Enzyme Inhibitors. Assessment of Treatment With Captopril and Enalapril Survival Study (ACESS).

Abstract: The present study examined the effect of treatment with angiotensin-converting enzyme inhibitors (ACEIs) on the long-term prognosis in 119 patients with dilated cardiomyopathy (DCM). Conventional therapy was used in 29 patients and 90 patients were treated with ACEIs: 50 were taking captopril and 40 were taking enalapril; 24 were taking ≥75 mg captopril or ≥20 mg enalapril daily (high-dose group) and 66 patients received smaller doses (low-dose group). No significant differences between groups were detected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In total, 25 observational studies (cohort studies) were identified. Two studies were excluded from the analysis because they included <100 patients [13, 14]. In total, 23 studies remained eligible for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 25 observational studies (cohort studies) were identified. Two studies were excluded from the analysis because they included <100 patients [13, 14]. In total, 23 studies remained eligible for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Dilated cardiomyopathy (DCM) is often accompanied by malignant ventricular arrhythmia, such as ventricular tachycardia and fibrillation, which is difficult to predict and is also the major cause of sudden cardiac death 1,2 . Angiotensin‐converting enzyme inhibitors (ACEI) have been shown to have beneficial effects on the long‐term outcome of DCM patients 3 . Treatment with ACEI has also been shown to reduce mortality in patients with other structural heart diseases, such as myocardial infarction and heart failure 4–7 .…”
Section: Introductionmentioning
confidence: 99%